The Effect of Work Discipline on Employee Productivity of PT Jalur Nugraha Ekakurir (JNE) Rantau Rasau Branch - Sisilia Dwi Ningsih; Anisa Fauziah (Jurnal Manajemen Bisnis dan Pariwisata, 2025)
This study focuses on examining the influence of work discipline on increasing employee productivity at PT Jalur Nugraha Ekakurir (JNE) Rantau Rasau Branch. The approach applied is a quantitative method, with simple linear regression analysis as the main tool. The research sample of 30 employees was selected using saturated sampling techniques. Data was collected through questionnaires using the Likert scale. From the data analysis, it appears that work discipline has a significant positive influence on productivity. This finding is supported by a calculated t-value of 5.162, which is higher than the table t-value of 2.052, and a significance value of 0.000 which is below 0.05. In addition, the coefficient of determination (R-Square) reaches 0.555, which means that work discipline contributes about 55.5% to employee productivity. The remaining 44.5% was influenced by other variables outside the scope of this study. Thus, work discipline seems to be a crucial element that requires serious attention from the company.